PERAN KELUARGA BEKERJA DALAM MENSOSIALISASIKAN NILAI AGAMA PADA ANAK DI RT 02 RW 02 DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Fitri Yulia; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Research on role of family work in socializing the value of religion in children in RT 02 RW 02, has a purpose to know the way families in socializing the value of religion in children. The research location is located at RT 02 RW 02 Tarai Bangun Village Tambang Sub District Kampar Regency. This study uses qualitative methods by analyzing the questions obtained and presented in the form of a systematic and scientific sentence. The process of analysis begins by reviewing all data that has been obtained from observations, and in-depth interviews of research informants then the data will be presented in the form of qualitative. Determination of subjects in this study using purposive sample technique. Where the samples are married couples who work and married couples who have children aged 5-13 years. The definition of concepts used in this research is the role, family and religious socialization. Indicators of this research is the way of family in socialize religious values of prayer fardu, fasting, reading al-qur'an, morals to parents, morals to others, socialization in dress and socialization in behaving. The results of this study describes the role of working families in socializing the religious values of children in RT 02 RW 02 is good enough. This can be seen from the socialization of the worship practice of the parent prayer teaches movement first and use the media images, socialization reading al-qur'an parents bring chaplain to the house, handed over completely to TPA / MDA and taught themselves at home. Socialization of morals to parents and neighbors is quite good as saying greeting when entering the house, politely speaking to parents and saying goodbye when out of the house and not doing deviant behavior, socialization in dressing well enough because parents give knowledge to children about how to dress up good according to the religion of Islam and in behaving parents apply to always keep hospitality like greeting an older man with a greeting that polite and courteous. However, it is expected that parents who work to further improve their attention to children especially in the socialization of religious values.Keywords: Role, Family and Socialization of Religion